Profile of PAP smears done in a tertiary centre in North Kerala - Elizabeth Thomas, Enid; Kumaran, Jayasree Anandabhavan (International Journal Of Community Medicine And Public Health, 2018)
Background: In India, cervical cancer is the second most common cancer among women. WHO sponsored expert group meeting on “Strategies for Cervical cancer Control” recommends women of 30-59 years as target group for cervical cancer screening in India. Statistics show us that routine cervical cancer screening is not happening in India. Methods: This is a retrospective, descriptive, record based study done in a private medical college in Northern Kerala to study the profile of PAP smears during the years, 2014 and 2015 and to find out the appropriateness of the recommendations for age for cervical cancer screening. The data regarding cervical smears were analyzed using Epi info software. Results: A total of 3059 cervical smears were analyzed retrospectively. The age group of the study population ranged from 21 years to 93 years with the mean age of 46.3942±13.7 SD. Of all the smears, 2993 (97.84%) were Negative for intraepithelial lesion or malignancy (NILM). A total of 66 smears (2.15%) showed epithelial abnormality. All precancerous lesions, LSIL (29.03%), HSIL (37.04%) and Atypia (37.5%) were most commonly found in the age group of 61-70 years. Conclusions: The incidence of epithelial abnormality is found increasingly in older age groups. Limiting the target population for screening to 30-59 years, will result in missing out of many cases with precancerous lesions which in turn may fail our attempts in reducing the burden of cervical cancer. So a higher age group as target population needs to be set.